(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
In SSP (stimulus-stimulus pairing), a target sound is paired with an item or event preferred by a child. As a possible result, children begin to imitate the presented sound. This study evaluated the effects of the guidance component on the effectiveness of SSP (stimulus-stimulus pairing) in children with ASD. A multiple baseline design across participants was used. Three children were subjected to two types of SSP: (A) without the requirement for an orienting response to the stimuli, and (B) SPP with the requirement for an orienting response. Sessions were held lasting 10 minutes, with a 1- minute interval between pairings. P3 and P2 had an increase in responses in B. For P1 the result was the opposite, there was greater vocalization of target responses in A. The data suggest relevance to the participants' initial repertoire, and consider that the increase in vocalizations may involve operant contingencies.